Side effects of COVID-19 vaccines among Iranian healthcare workers: a retrospective cohort study - Roudgari, Hassan; Etemad, Koorosh; Karami, Manoochehr; Mostafavi, Farideh; Sotoodeh Ghorbani, Sahar; Farhadi Babadi, Kosar; Rahimi, Elham; Taherpour, Niloufar; Fattahi Masoom, Seyed Mahmood; Habibi, Masoud; Kermanpour, Hossein; Laripour, Reza; et al. (The Journal of Infection in Developing Countries, 2024)
Introduction: This study assessed the incidence and severity of side effects associated with coronavirus disease 2019 (COVID-19) vaccination among healthcare workers registered with the Medical Council of the Islamic Republic of Iran. Methodology: A retrospective cohort study was conducted on the healthcare workers focusing on the side-effects of COVID-19 vaccines from March to June 2021. Data were collected using online questionnaires. Multivariable logistic regression was used to assess the association between side effects of the vaccines and demographic variables, comorbidities, vaccine type, and history of COVID-19. Results: Out of 42,018 people who were included, 55.85% reported at least one side effect after receiving the first vaccine dose. 4.59% of those with side effects sought diagnostic intervention or were referred to treatment centers. Multivariable logistic regression indicated that being a woman, higher education, having a history of COVID-19 infection, and having comorbidities increased the risk of side effects. The AstraZeneca vaccine significantly increased the risk of side effects compared to the Sputnik vaccine, while the Sinopharm vaccine decreased this risk. The risk of developing a side effect decreased with age. The risk of moderate and severe side effects was significantly associated with gender, younger age, comorbidities, and a history of COVID-19 infection. Moderate and severe side effects were less reported by those who received the Sinopharm vaccine. Conclusions: Clinical complications after COVID-19 vaccination, directly or indirectly caused by the vaccines, are common. However, the benefits of COVID-19 vaccines greatly outweigh the risk of reversible side effects, especially among the high-risk population.